Physicochemical, bioactive, and sensory properties of persimmon-based ice cream: Technique for order preference by similarity to ideal solution to determine optimum concentration - Karaman, Safa; Toker, Omer Said; Yuksel, Ferhat; Cam, Mustafa; Kayacier, Ahmed; Dogan, Mahmut (ELSEVIER SCIENCE INC, 2014)
In the present study, persimmon puree was incorporated into the ice cream mix at different concentrations (8, 16, 24, 32, and 40%) and some physicochemical (dry matter, ash, protein, pH, sugar, fat, mineral, color, and viscosity), textural (hardness, stickiness, and work of penetration), bioactive (antiradical activity and total phenolic content), and sensory properties of samples were investigated. The technique for order preference by similarity to ideal solution approach was used for the determination of optimum persimmon puree concentration based on the sensory and bioactive characteristics of final products. Increase in persimmon puree resulted in a decrease in the dry matter, ash, fat, protein contents, and viscosity of ice cream mix. Glucose, fructose, sucrose, and lactose were determined to be major sugars in the ice cream samples including persimmon and increase in persimmon puree concentration increased the fructose and glucose content. Better melting properties and textural characteristics were observed for the samples with the addition of persimmon. Magnesium, K, and Ca were determined to be major minerals in the samples and only K concentration increased with the increase in persimmon content. Bioactive properties of ice cream samples improved and, in general, acetone-water extracts showed higher bioactivity compared with ones obtained using methanol-water extracts. The technique for order preference by similarity to ideal solution approach showed that the most preferred sample was the ice cream containing 24% persimmon puree.
Keywords: persimmon; ice cream; bioactivity; technique for order preference by similarity to ideal solution; INVERTASE ACTIVITY; SUGAR CONTENT; ANTIOXIDANT; PEEL; VANILLA; QUALITY; FRUITS; FIBER; AHP; Agriculture; Food Science & Technology